China – Angola – Russia: Non-existing Triangle - A. Dikarev (Международная аналитика)
This article contains the detailed comparative analysis of Russian and Chinese participation in the economic development of one of the most important African countries. The article highlights the history of credits and loans, foreign direct investments to Angola, dynamics of Russian and Chines trade turnover in the 21-st century. Main projects of Russia-Angola economic co-operation, activities of the biggest Chinese companies in Angola are in the scope of this research. Main economic interest of both powers – China and Russia – is to obtain access to the rich energy and mineral resources of Angola. However, any numerical indices of Russian and Chinese involvement into Angolan economics show that Russia cannot compete with China in this respect. Incomparable scale of trade turnover and economic cooperation make the hypotheses about possible “rivalry” between Russia and China in this region groundless. In spite of the fact that China has reduced loans volumes to Angola recently, the trade between the two countries shows increasing trend. For the time being Russia seems competitive to China in military cooperation with Angola though falls behind in humanitarian sphere.